0=(m+4)(m-4)

Simple and best practice solution for 0=(m+4)(m-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=(m+4)(m-4) equation:



0=(m+4)(m-4)
We move all terms to the left:
0-((m+4)(m-4))=0
We add all the numbers together, and all the variables
-((m+4)(m-4))=0
We use the square of the difference formula
m^2+16=0
a = 1; b = 0; c = +16;
Δ = b2-4ac
Δ = 02-4·1·16
Δ = -64
Delta is less than zero, so there is no solution for the equation

See similar equations:

| -1+16n=10n-19 | | 7m-20m-10=3 | | (Y-0)=16(x-2) | | 4=z-11/4 | | 10m-2/5=9.60 | | 54+89+x/3=76 | | Y-0=16(x-2) | | 9x=-x+8 | | -13j-12=-12j | | -6t-5=-7t-11 | | 1/2x-2/3=3/4x+1/2 | | -15w=-16-7w | | -15w=-16–7w | | 37+2x=180 | | -16j=-18j+12 | | 54=(4x+6)(2x) | | t+11/2=-4 | | 6x^2-18x-98=0 | | 18n+-11n-18=-3 | | 20+7h=6h | | 3b+5=6b-3b+8-9 | | 5k-10=7k+8 | | -18=-3(h-9) | | (X+4)+3(5-2x)=11 | | 20-9k=-20+11k | | 15n-6n=9 | | 9w+10=w-10+10w | | 10r=-7+11r | | 4x/3x-12=1/x-4 | | b/3+-15=-13 | | 3x+7=14+2.5x | | x-31/8=98/9 |

Equations solver categories